2021
DOI: 10.3390/insects12070628
|View full text |Cite
|
Sign up to set email alerts
|

More Power with Flower for the Pupal Parasitoid Trichopria drosophilae: A Candidate for Biological Control of the Spotted Wing Drosophila

Abstract: Parasitoids are currently considered for biological control of the spotted wing drosophila (SWD) in berry crops. Releases of mass-reared parasitoids require the presence of all resources necessary to ensure their effectiveness in the crop system. The use of floral resources to feed Trichopria drosophilae, one of the candidate species, was investigated in a laboratory study. The life expectancy of males and females increased by three to four times when they had access to flowers of buckwheat or of two cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
(61 reference statements)
0
11
0
1
Order By: Relevance
“…[28][29][30] It has been demonstrated that D. suzukii survival is enhanced when they had access to alyssum, as the proboscis is sufficiently long to reach the nectaries and feed on the nectar they contain. 13 Although the nectaries of the buckwheat control mix may have been more readily accessible to D. suzukii, clearly alyssum provides supplemental resources as well. 13 Another possible explanation for our results is phenological mismatches between early season berry crops, D. suzukii, and its associated parasitoids.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[28][29][30] It has been demonstrated that D. suzukii survival is enhanced when they had access to alyssum, as the proboscis is sufficiently long to reach the nectaries and feed on the nectar they contain. 13 Although the nectaries of the buckwheat control mix may have been more readily accessible to D. suzukii, clearly alyssum provides supplemental resources as well. 13 Another possible explanation for our results is phenological mismatches between early season berry crops, D. suzukii, and its associated parasitoids.…”
Section: Discussionmentioning
confidence: 99%
“…13 Although the nectaries of the buckwheat control mix may have been more readily accessible to D. suzukii, clearly alyssum provides supplemental resources as well. 13 Another possible explanation for our results is phenological mismatches between early season berry crops, D. suzukii, and its associated parasitoids. Studies that have monitored D. suzukii populations across growing seasons have found that populations peak depending on the climate of the area sampled, but generally occur around July or August.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations